Factors affecting fertility choice among married couples in Oton, Iloilo. - Autentico, Sheila Mulato
This study identified the different factors affecting fertility choice of married couples in Oton, Iloilo. There were 100 participants from the three barangays in Oton, Iloilo namely : Trapiche, Poblacion South, and Buray. The dependent variable is measured by the actual number of living children the married couples have. The independent variables were classified into four categories : economic factors, biological factors, psychological factors, and geographical factors. The multivariate analysis revealed that the significant variables found to significantly affect the decision on the number of children married couples (at 5% level significance) are gross monthly income of the household, years of formal education of the wife, age of wife at first marriage, ideal number of children by the couple and perception of children to be help in old age. However, the R-squared value 0f 30.78 indicates that there are still some factors that were not included in the model. Nevertheless, the significant variables had the expected signs.